Students’ Perception on Artificial Intelligence Use in Learning Process (Case Study of PAI Students at Singaperbangsa University Karawang) - Farida, Nur Aini; Makbul, M. (Proceeding International Conference on Religion, Science and Education, 2024)
Artificial Intelligence is the ability of a machine to display human-like capabilities such as reasoning, learning, planning and creativity. Nowaday, the usage of Artificial Intelligence is rising. Artificial Intelligence (AI) technology has become increasingly important in the modern world due to its numerous applications and benefits and is quickly changing how we live our lives. This study aims to understand the students’ perception on AI use in enhanching students’ learning process. This study is a qualitative descriptive research which try to potray the students’ perception on AI. In the field of education, Artificial intelligence has the potential to transform education by enabling personalized learning and improving student outcomes substantially. Results shows that most of students’ think that Artificial Intelligence is a very powerful tool to improve and to enhace their learning process. Artificial Intelligence helps them to find learning sources easier, faster, and more comprehensive. On the other hand, some of students stated that Artificial Intelligence could lead to dependency on Artificial Intelligence, declining critical analysis, and lazyness.